Identification of Plankton Diversity and Abundance at Situ Gintung South Tangerang City - Fatmala, Qori Diah; Aisyah, Arina; Afandi, Ahmad Yusuf (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Plankton are organisms that are found living floating in the water, that move passively so they are easily carried by currents. Plankton includes two large groups, namely phytoplankton which is similar to plants and zooplankton which similar to animals. One of important benefits of plankton is an indicator of biological conditions. This research aims to determine the types of plankton and their abundance at Situ Gintung, South Tangerang City. Sampling was conducted at three points area. The samples obtained were then observed and counted under a microscope and identified using web determination. Data were analyzed using plankton diversity and abundance formulas. The research results found phytoplankton species, such as Nitzschia sp., Navicula sp., Coscinodiscus sp., Synedra sp., Staurastrum sp., Scenedesmus sp., Coelastrum sp., Oscillatoria sp., Spirulina sp., Peridinium sp., and Phacus sp. The zooplankton obtained were Nauplius sp., Eudiaptomus sp., Polyarthra sp., Brachionus sp., Trichocerca sp., and Lecane sp. The average value of the phytoplankton diversity index is 0.543 and zooplankton is 1.043. The average phytoplankton abundance index obtained is 18,808,334 ind/L and zooplankton is 32,766 ind/L. Based on the results obtained, it was concluded that there were 11 types of phytoplankton and 6 types of zooplankton. The phytoplankton diversity index is in the low category and zooplankton is in the medium category, while the phytoplankton and zooplankton abundance index are in the medium to high category, but phytoplankton abundance is more dominant than zooplankton.